Data Security Using Crypto Bipartite Graph Theory with Modified Diffie–Hellman Algorithm - Shastri, V. Harsha; Pragathi, C. (Wireless personal communications, 2024)
Sharing confidential information over an unprotected channel is prone to privacy breaches since unauthorized parties can steal the data. Therefore, developing a cryptosystem that ensures the security criteria for transmitted data’s secrecy, integrity, and validity is necessary and inevitable. This paper proposes a unique graph-based crypto-system to guarantee data integrity during user-to-user communication. In the proposed work, the data is encrypted using a crypto bipartite graph theory (CBGT), which uses a creative strategy to safeguard communication by utilizing the structural characteristics of bipartite graphs. Random key selection may result in poor security and lead the CBGT to potential cryptographic attacks. In a CBGT based cryptosystem, the key is a set of edges that join the vertices belonging to the two sets. Here, improved teacher learning based optimization (iTLBO) is used to select a secure and optimized set of edges, which improves the encryption security without compromising the decryption efficiency. Moreover, a modified Diffie Hellman (m-DH) algorithm is used for key exchange. Here, Euler’s coefficient and modulo inverse are used in the private key generation to strengthen the m-DH security. Python is used to implement the simulations, and the outcomes demonstrate that the proposed method performs better than existing methods like Data Encryption Standard (DES), Advanced Encryption Standard (AES), Blowfish, and Rivest–Shamir–Adleman (RSA) in terms of encryption time, decryption time, execution time and throughput.